Infographic data visualization as an alternative form of news: content analysis of Covid-19 vaccine issues of data journalism-based media - Sika Nur Indah; Khuswatun Hasanah (The Indonesian Journal of Communication Studies, 2022)
Vaccines and vaccinations have become the issues taking over the media coverage during the Covid-19 pandemic. The media deliberately displays data visualizations in the form of infographics to help the audiences understand the situation in a less complicated way. This study aims to identify messages conveyed through visualizations of infographic data in data journalism-based media in Indonesia. The samples of infographic contents were acquired through the information posted by the official Instagram accounts of katadata.co.id (@katadatacoid) and tirto.id (@tirtoid) as media that declared themselves to practice data journalism. The research method used in the study was content analysis using descriptive statistical analysis. The results of the study show that vaccine and vaccination issues are presented with statistical-based, as well as writing elements, background info, graphics, photos, icons, and diagram elements; the infographic includes elements of news completeness, such as using 5W+1H questioning method (what, who, where, when, why, and how) and mentioning credible sources; Infographic is an alternative way of reporting news during a pandemic. In addition, this research is expected to contribute to the media in making editorial reporting policies in the digital era, especially related to pandemic issues.